Strategy and Society: Corporate Social Responsibility (CSR) to the Revolving Fund Program - Windhi Tia Saputra; Yul Tito Permadhy; Fitria Ayuningtyas; Niken Ridianti (Asian Social Work Journal, 2021)
This research was conducted to evaluate the Implementation of Corporate Social Responsibility (CSR) in the existing education program at PT FIFGROUP, as a program to help improve SME entrepreneurs' quality of business located around the company, especially in Cilandak Sub-district, South Jakarta. The theory used in this research is Corporate Social Responsibility. The method used in this research is qualitative, a case study approached, and the type of research descriptive. The data collection technique is in-depth interviews with Key Informant and Informants as well as methods of data validity by source. The results obtained in this research used the stages of Corporate Social Responsibility (CSR). The results of program activities have been running well by its purpose and benefits. The conclusion of the results of this research indicated that MSME entrepreneurs (micro, small and medium enterprises) got helped by the revolving fund program as assistance in improving the business. It is implemented by the stage of the implementation of Corporate Social Responsibility (CSR) and PT FIFGROUP doing continuous improvement to spread revolving funds to SME entrepreneurs (micro, small and medium enterprises) that eligible and promptly.